(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
The issue faced by the community partners of the two schools, namely Lalumpe Elementary School and Kombi Junior High School, in Lalumpe Village, Kombi District, Minahasa Regency, is the lack of clean water and limited electricity supply. The proposed solution for the clean water and electricity crises is the implementation of appropriate technology using solar-powered water pumps. The program offered by the Implementation Team for Community Service aims to apply, train, and provide assistance in appropriate technology using solar energy-powered water pumps, facilitated by the Center for Renewable Energy at Sam Ratulangi University. The objective of this Community Service Program is to implement appropriate technology based on renewable energy, specifically solar-powered water pumps, which can serve as a target for training and mentoring for students and faculty members at these two schools that located in rural and remote areas in North Sulawesi provience of Indonesia.